The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1016/j.jns.2020.116826
|View full text |Cite
|
Sign up to set email alerts
|

Novel likely disease-causing CLN5 variants identified in Pakistani patients with neuronal ceroid lipofuscinosis

Abstract: Background Neuronal ceroid lipofuscinosis (NCL) is a hereditary lysosomal storage disease with progressive brain neurodegeneration. Mutations in ceroid lipofuscinosis neuronal protein 5 (CLN5) cause CLN5 disease, a severe condition characterized by seizures, visual failure, motor decline, and progressive cognitive deterioration. This study aimed to identify causative gene variants in Pakistani consanguineous families diagnosed with NCL. Methods After a thorough clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Cerebella from human CLN6 patients may be normal or show some atrophy (Cannelli et al, 2009;Peña et al, 2001), but it has been reported that the cerebellum in human CLN5 cases can be severely atrophied, with an almost complete depletion of cerebellar granule and Purkinje cells observed in post mortem tissue (Goebel et al, 1999;Haltia, 2003;Tyynelä et al, 1997). Brain imaging of human CLN5 patients reveals the same moderate-to-severe cortical atrophy seen in CLN5 animal models, but marked atrophy of the human cerebellum is one of the most striking abnormalities (Autti et al, 1992;Azad et al, 2020;Bessa et al, 2006;Lauronen et al, 2002;Mancini et al, 2015;Simonati et al, 2017). This is not the case for most animal CLN5 and CLN6 NCLs.…”
Section: Discussionmentioning
confidence: 99%
“…Cerebella from human CLN6 patients may be normal or show some atrophy (Cannelli et al, 2009;Peña et al, 2001), but it has been reported that the cerebellum in human CLN5 cases can be severely atrophied, with an almost complete depletion of cerebellar granule and Purkinje cells observed in post mortem tissue (Goebel et al, 1999;Haltia, 2003;Tyynelä et al, 1997). Brain imaging of human CLN5 patients reveals the same moderate-to-severe cortical atrophy seen in CLN5 animal models, but marked atrophy of the human cerebellum is one of the most striking abnormalities (Autti et al, 1992;Azad et al, 2020;Bessa et al, 2006;Lauronen et al, 2002;Mancini et al, 2015;Simonati et al, 2017). This is not the case for most animal CLN5 and CLN6 NCLs.…”
Section: Discussionmentioning
confidence: 99%
“…Our patient had CLN5 variant that creates a premature stop codon causing non sense mutation 5,6 . Azad B, et al recently reported novel likely disease causing CLN5 variants in Pakistani patients with NCL 7 .…”
Section: Case Reportmentioning
confidence: 98%